Two clinopyroxenes from Upper Swat: Their chemistry and its petrogenitic implications - Hamidullah, Syed; Khan, M. Javed (Journal of Himalayan Earth Sciences, 1993)
TWO sets of clinopyroxene analyses, one from the andesite of Utror volcanics and other from a troctolite patch in diorite from Deshai, Upper Swat, are used to ascertain the magmatic affinity and tectonic setting of their host rocks. Both the sets indicate igneous crystallization in island arc-related oroganic environments. Clinopyroxene data from the volcanic rock indicate calc-alkaline affinities, while, those from troctolite appear to have grown from a tholeiitic magma.